2005
DOI: 10.1212/01.wnl.0000150903.38639.e1
|View full text |Cite
|
Sign up to set email alerts
|

Do the Brain Attack Coalition’s criteria for stroke centers improve care for ischemic stroke?

Abstract: Of the 11 stroke center elements recommended by the BAC, 7 were associated with increased tPA use. Institutions with a greater number of these seven features used tPA more often, suggesting these key elements may be most important for primary stroke center designation, at least in terms of identifying centers that deliver IV tPA frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 40 publications
7
91
0
1
Order By: Relevance
“…One study on patient outcome has tested the Brain Attack Coalition PSC criteria. 20 This US multicenter study based on university hospital discharge registries (nϭ16 853) showed an association with PSC criteria and increased rate of thrombolysis, but no association with in-hospital mortality was observed, possibly due to a short median follow-up of 5 days. Other studies have associated stroke center designation with better process indicators of stroke care and increased rate of thrombolysis, [21][22][23] but no correlation with patient outcome and Brain Attack Coalition stroke center criteria has been demonstrated before our study.…”
Section: Meretoja Et Al Effectiveness Of Stroke Centersmentioning
confidence: 71%
“…One study on patient outcome has tested the Brain Attack Coalition PSC criteria. 20 This US multicenter study based on university hospital discharge registries (nϭ16 853) showed an association with PSC criteria and increased rate of thrombolysis, but no association with in-hospital mortality was observed, possibly due to a short median follow-up of 5 days. Other studies have associated stroke center designation with better process indicators of stroke care and increased rate of thrombolysis, [21][22][23] but no correlation with patient outcome and Brain Attack Coalition stroke center criteria has been demonstrated before our study.…”
Section: Meretoja Et Al Effectiveness Of Stroke Centersmentioning
confidence: 71%
“…[5][6][7][8] To date, only one study in Finland has reported lower 1-year stroke case-fatality associated with stroke centers. 26 Our study extends the findings from this prior study, as systems of stroke care in the U.S. may differ substantially from other national healthcare systems (especially those with universal health coverage).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Prior studies have largely focused on stroke processes of care, such as treatment timeline and use of thrombolytic therapy. [5][6][7][8] There is comparably less information on whether or not better care at stroke centers affects acute or long-term mortality. 9 Therefore, our goal was to evaluate the association between admission to stroke centers for acute ischemic stroke and mortality.…”
mentioning
confidence: 99%
“…Those hospitals achieving PSC certification have been shown to have significant increases in IV thrombolysis rates as well as improved 30-day mortality and readmission outcomes. [27][28][29][30][31][32][33] Thus, the efforts by these 2 hospitals to achieve and maintain PSC status likely contributed to the abrupt rise in tPA use observed in the community. In previous studies, there have been conflicting data concerning sex differences in tPA use.…”
mentioning
confidence: 99%